2009
DOI: 10.1186/1743-422x-6-116
|View full text |Cite
|
Sign up to set email alerts
|

Sequence diversity on four ORFs of citrus tristeza virus correlates with pathogenicity

Abstract: The molecular characterization of isolates of citrus tristeza virus (CTV) from eight locations in Mexico was undertaken by analyzing five regions located at the opposite ends of the virus genome. Two regions have been previously used to study CTV variability (coat protein and p23), while the other three correspond to other genomic segments (p349-B, p349-C and p13). Our comparative nucleotide analyses included CTV sequences from different geographical origins already deposited in the GenBank databases. The larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…GLRaV-2 sequences were classified into six genetic groups including isolates from: (I) China, USA, Brazil, Italy, Poland, and South Africa, (II) Italy and South Africa, (III) USA, Italy, and Brazil, (IV) Italy and France, (V) USA, and (VI) Italy (Figure 1C). Finally, the citrus-infecting CTV, the best studied virus in the family, with CP sequences of almost 600 worldwide isolates (Albiach-Martí et al, 2000; Rubio et al, 2001b; Alavi et al, 2005; Roy et al, 2005; Sorrentino et al, 2005; Papayiannis et al, 2007; Iglesias et al, 2008; Jiang et al, 2008; Černi et al, 2009; Herrera-Isidrón et al, 2009; Oliveros-Garay et al, 2009; Fisher et al, 2010; Harper et al, 2010; Matos et al, 2013), showed a moderate genetic variability. All isolates fell into a single genetic group, albeit this could be divided into five to seven subgroups (Figure 1C), some of them very homogeneous (isolates with almost identical sequences).…”
Section: Resultsmentioning
confidence: 99%
“…GLRaV-2 sequences were classified into six genetic groups including isolates from: (I) China, USA, Brazil, Italy, Poland, and South Africa, (II) Italy and South Africa, (III) USA, Italy, and Brazil, (IV) Italy and France, (V) USA, and (VI) Italy (Figure 1C). Finally, the citrus-infecting CTV, the best studied virus in the family, with CP sequences of almost 600 worldwide isolates (Albiach-Martí et al, 2000; Rubio et al, 2001b; Alavi et al, 2005; Roy et al, 2005; Sorrentino et al, 2005; Papayiannis et al, 2007; Iglesias et al, 2008; Jiang et al, 2008; Černi et al, 2009; Herrera-Isidrón et al, 2009; Oliveros-Garay et al, 2009; Fisher et al, 2010; Harper et al, 2010; Matos et al, 2013), showed a moderate genetic variability. All isolates fell into a single genetic group, albeit this could be divided into five to seven subgroups (Figure 1C), some of them very homogeneous (isolates with almost identical sequences).…”
Section: Resultsmentioning
confidence: 99%
“…The risks of spreading these severe isolates to new areas by propagation or nursery trees are real and should be considered (Herrera-Isidrón et al, 2009). Therefore, losses can only be effectively reduced and prevented by an efficient system of preimmunization against these severe isolates (Sambade et al, 2002;Moreno et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For amplification of the CP genomic region (672 bp), reverse transcription polymerase chain reaction (RT-PCR) with set of primers IRA1 5'ATGGACGAC-GAAACAAAGAAATTG3' and IRA2 5'GCTCAACGTGTGTTAA3' [16] was used. To generate the cDNA, approximately 200 ng of total RNA were denatured at 95˚C for 5 min.…”
Section: Amplification Of the Cp Genomic Regionmentioning
confidence: 99%
“…The maximum parsimony and Bayesian inference method were used to generate the phylogenetic tree for the CP region including the following full length CTV sequences: T36 [11] and T30 from Florida [29], VT from Israel [30], T385 from Spain [31], SY568 from California [32], NUagA from Japan [33], CTV from Mexico [34], NZ-M16 and NZ-B18 from New Zealand [35]; and CP sequences from Mexico: TAM11, NL8, VER2-2, QR2753-1, BC15-1, MichL9A11/9-1, Colima 1997 and Yucatán 2000 [16].…”
Section: Phylogeny Of Ctv Isolatesmentioning
confidence: 99%
See 1 more Smart Citation